SLCO3A1, A novel crohn's disease-associated gene, regulates nf-κB activity and associates with intestinal perforation. - Shu-Chen Wei; Yan-Yin Tan; Meng-Tzu Weng; Liang-Chuan Lai; Jen-Hao Hsiao; Eric Y Chuang; Chia-Tung Shun; Deng-Cheng Wu; Ai-Wen Kao; Chiao-Shung Chuang; Yen-Hsuan Ni; Ming-Jium Shieh; et al. (PLoS ONE)
Background & aims To date, only one gene (TNFSF15) has been identified and validated as a Crohn's disease (CD)-associated gene in non-Caucasian populations. This study was designed to identify novel CD-associated single nucleotide polymorphisms (SNPs)/genes and to validate candidate genes using a functional assay. Methods SNPs from 16 CD patients and 16 age- and sex-matched control patients were analyzed using Illumina platform analysis. Subsequently, we expanded the study and followed 53 CD patients and 41 control patients by Sequenom MassArray analysis. Quantitative PCR and immunohistochemical staining were performed to assess mRNA and protein expression of the candidate gene on tissue isolated from CD patients. Genotype was correlated with CD phenotypes. Finally, the candidate gene was cloned and its effect on NF-κB activity assessed using a reporter luciferase assay. Results SLCO3A1 (rs207959) reached statistical significance in the first-stage analysis (P = 2.3E-02) and was further validated in the second-stage analysis (P = 1.0E-03). Genotype and phenotype analysis showed that the rs207959 (T) allele is a risk allele that alters SLCO3A1 mRNA expression and is associated with intestinal perforation in CD patients. Higher levels of mRNA and protein expression of SLCO3A1 were seen in CD patients compared with the control group. Overexpression of SLCO3A1 induced increased NF-κB activity and increased phosphorylation of P65, ERK, and JNK. Nicotine augmented the activation of NF-κB in the presence of SLCO3A1. Conclusions SLCO3A1, a novel CD-associated gene, mediates inflammatory processes in intestinal epithelial cells through NF-κB transcription activation, resulting in a higher incidence of bowel perforation in CD patients.